Formal versus material ontologies for information systems interoperation in the semantic web - Colomb, Robert M. (Oxford University Press, 2006)
Information systems ontology is intended to facilitate interoperability among the many applications which are now becoming available on the Internet. In particular, it is intended to facilitate the development of intelligent agents which can automate a large part of the task of a user achieving some end employing multiple autonomous applications. A large number of ontologies exist supporting specific kinds of interoperation among selected, generally mutually aware, applications. The intent of the upper ontology movement is to develop an abstract description of what there is in the world, in an application-independent form, which can be used both to help build specific ontologies and to help in finding common ground among them. This paper argues that, for the purposes of information systems interoperation and the semantic web, application-independent upper ontologies are unlikely to be successful because of semantic heterogeneity. However, the paper argues for a distinction in upper ontologies between formal and material ontologies, based on analogies with concepts in Kant's synthetic a priori, and that formal ontologies whose focus is on how we see the world are more likely to be successfully developed in the absence of applications than are material ontologies, which attempt to catalog the world a priori. Categories and Descriptors: C.2.4 [Distributed Systems] Distributed Applications, Distributed Databases D.2.12 [Software Engineering] Interoperability - Data Mapping; H.3.5 [Information Storage and Retrieval] Online Information Services - Data Sharing and Web-based Services; H.2.1 [Database Management] Systems.